2022
DOI: 10.1002/app.52466
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically enhanced poly(lactic acid)/polyurethane blend with interfacial‐localized clay particles

Abstract: In this study, clays (C30B, C20A, and ) with different interlayer modifier and localization are investigated to improve mechanical properties of poly(lactic acid) (PLA)/thermoplastic polyurethane (TPU) blend based on crystallization, morphology, and rheology analyses. The mechanical properties of the PLA/TPU 70/30 blend (elongation at break: 229%, impact strength: 55 J/m) are additionally increased by the clay particles. Depending on modifiers within the particles localized at the interface, 0.1 wt% of the C30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 66 publications
(136 reference statements)
0
1
0
Order By: Relevance
“…[22] Although PLA-based FDM 3D printing is well researched, certain challenges such as brittleness, low thermal stability, sluggish crystallization rate, poor melt strength, lack of flexibility and elasticity, and mechanical anisotropy, among other issues, limit the industrial applications of PLA 3D printed objects. [23] Attempts to mitigate these drawbacks by including nanoscale additives such as nanocrystalline cellulose, [24] cellulose nanofibers (CNFs), [25] carbon nanotubes (CNTs), [26] graphene, [27,28] and so on have met with some success. In one of the recent research publications by Ambone et al, [25] PLA/CNF composite filament was 3D printed, and they observed an improvement of 84% in tensile strength and 63% in tensile modulus with the addition of 1 wt% CNF.…”
Section: Introductionmentioning
confidence: 99%
“…[22] Although PLA-based FDM 3D printing is well researched, certain challenges such as brittleness, low thermal stability, sluggish crystallization rate, poor melt strength, lack of flexibility and elasticity, and mechanical anisotropy, among other issues, limit the industrial applications of PLA 3D printed objects. [23] Attempts to mitigate these drawbacks by including nanoscale additives such as nanocrystalline cellulose, [24] cellulose nanofibers (CNFs), [25] carbon nanotubes (CNTs), [26] graphene, [27,28] and so on have met with some success. In one of the recent research publications by Ambone et al, [25] PLA/CNF composite filament was 3D printed, and they observed an improvement of 84% in tensile strength and 63% in tensile modulus with the addition of 1 wt% CNF.…”
Section: Introductionmentioning
confidence: 99%